Penerapan UML Dalam Official Sistem Suatu Kost Berbasis Website - Sanjaya, Roy Bagus; Voutama, Apriade (Faculty of Computer Science, University of Jember, 2024)
The boarding house business is one of the profitable businesses, especially in places where the majority of residents are from outside, the more outsiders who come, the more the boarding house business will grow. However, with the large number of boarding house residents, a boarding house requires a website that regulates the boarding house system so that it makes it easier for both the owner and the boarding house residents in it. The development of this boarding house system will be one of the keys to getting out of this problem and the development of the boarding house aims to facilitate activities in it so that the ongoing business process can run efficiently. With the existence of this boarding house system website, it can speed up boarding house owners in recording all data related to boarding houses or boarding house residents who rent. The design of the boarding house system in the future will be very useful during the running of the boarding house business and the data collection in it.